Frontiers of combining systems : 12th international symposium, FroCoS 2019, London, UK, September 4-6, 2019 : proceedings /: 12th international symposium, FroCoS 2019, London, UK, September 4-6, 2019 : proceedings. ([2019]) - Unknown
No abstract available